EFFECT OF POLYETHYLENE MOLECULAR MASS CHARACTERISTICS ON SLIP EFFECT - A. A. Yurkin; I. D. Simonov-Emelyanov; P. V. Surikov; N. L. Shembel (Тонкие химические технологии)
The rheological properties of polyethylene with different molecular weight characteristics were studied. Difference of molecular weight characteristics was found on the basis of melt flow index, and slip effect in the molten polyethylene flow was studied. The presence of slip effect is found in case of flowing polyethylene with a higher molecular weight in contrast to polyethylene with lower molecular weight at different temperatures. Changes of the slip effect parameters upon mixing polyethylenes with very much different molecular weight characteristics were studied.